Factores que delimitan el aprendizaje en las clases on-line de los estudiantes de la Unidad Educativa Carlos Alberto Aguirre Aviles durante el periodo 2021 - 2022 - Fajardo Orellana, Yolanda Yamile (2022)
The present investigative work seeks to study the factors that delimit the learning of online classes of students in the Carlos Alberto Aguirre Aviles Educational Unit whose general objective is to analyze the different factors that help the formation of learning by relating them directly to ICTs and their domain. in the students. The problem that the student currently has to connect to online classes and their difficulty in learning will also be identified, the needs that each student has, the different reasons that prevent them from promoting their academic training, the lack of support from the family. The results obtained in the online survey addressed to the students of the educational institution of study that will defend the theoretical support of the investigative work will be analyzed. Coming to the conclusion of the link that exists between economic factors, technological factors and psychological factors that hinder the learning of students in the classes. Finally, come to the recommendations that will be taken into account for the future training of students in online classes and not have the same problem again within the educational institution.